If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -10x = 2x + -4 Combine like terms: 8x + -10x = -2x -2x = 2x + -4 Reorder the terms: -2x = -4 + 2x Solving -2x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x = -4 + 2x + -2x Combine like terms: -2x + -2x = -4x -4x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -4x = -4 + 0 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 5x+4-9=180 | | 6+7x=26+3x | | -16=-4(2x-8) | | 7x+4=6y+5 | | 6(2a)=3 | | 15x+12=7x-52 | | 9*8+10= | | 5(w-4)-8w=4 | | d+d+d=9 | | 17+7=a+8 | | 9*8-10= | | 2x-6=6x-14 | | 1.8Q-4.7-1.6Q=-0.8Q-4.1 | | 2236000-17740r=3500000 | | 8x+3-10x=-2(x-2)+x | | 34+5x=99 | | 5(w-4)-8=14 | | 0.6x-10=104x-14 | | 5=x^2-441 | | x+16(x-1)=7(3+x) | | 3+m=29 | | (2w^2+2w)+(9w^2+4w+3)= | | 5(x-3)+2k=41 | | 27+5s=189 | | (2w^2+2w)+(9w^3+4w+3)= | | -10x-10+3x=18 | | 39x+2=158 | | -2(8+2x)=-28 | | 4+8x=126 | | y-20=-42 | | 5x=8-12x+6 | | 25x+15=90 |